Isolated Tubal Torsion: Case Report and Review of the Literature - Kavak, Ebru Celik; Baykus, Yakup; Cim, Numan; Kavak, Salih Burcin; Ilhan, Rasit (Derman Medical Publ, 2015)
Isolated tubal torsion is a rare clinical entity causing acute pelvic pain. Preoperative diagnosis is difficult since it doesn't have any pathognomonic symptom, clinical sign, imaging or laboratory sign. It is mostly seen in women of reproductive age and mostly diagnosed during surgery done to find the etiology of acute abdomen. Since delay in diagnosis and treated can cause problems in fertility, it must be remembered in mind in differential diagnosis of acute abdomen especially in nulliparous women and in those who didn't complete their fertility.
Keywords: Isolated Tubal Torsion; Acute Abdomen; Ultrasono graphy